The study of collection durum winter wheat samples according to grain quality in the Rostov region - A. S. Kameneva; E. V. Ionova; D. M. Marchenko; N. P. Ilichkina; O. A. Nekrasova (Зерновое хозяйство России)
The success of any agricultural crop breeding, including winter durum wheat primarily depends on the initial material at the breeder’s disposal, its value, and the degree of study. The purpose of the current study was to evaluate collection samples of winter durum wheat according to quality indicators and to select the best ones for use in breeding programs. In the Rostov region there were studied 159 winter durum wheat samples of different ecological and geographical origin according to grain quality (protein percentage, gluten content, amount of carotenoid pigments, kernel hardness, nature weight). The winter durum wheat samples had a high protein percentage and belonged to the 1-st quality class. According to gluten content in grain there were identified 17 (10.7%) samples. The following samples had the maximum values of trait ‘SDS-sedimentation’: ‘588/15’ (Russia) with 50 ml; ‘SAHINBEY’ (Turkey), ‘SARI BUGDAY 2’ (Turkey), ‘543/15’ (Russia) with 49 ml; ‘ANKARA 98’ (Turkey) with 48 ml. The following 43 winter durum wheat samples (more than 85%) had large kernel hardness in the trial: ‘663/17’, ‘1121/12’, ‘Novinka 4’, ‘Alena’ (Russia), ‘C1252’ (Turkey), ‘SN TURK MI 82-83 90 / GUTROS-2’, ‘DF 28.82.84 / DAB-18’, ‘P 1290493 // HUI // AV79’ (Mexico), ‘K-61869’ (Moldova). Over the years of study, a large amount of carotenoid pigments was identified in the following samples: ‘Novinka 4’ with 705 μg /%, ‘535/17’ with 689 μg /%, ‘543/15’ with 664 μg /% (Russia), ‘OSU-3880001 / 4AOS / SNIP / 3 / MEDIUM / KIF // SAPI’ with 704 μg /% (Mexico), ‘Winter Gold’ with 697 μg /% (Germany). According to the complex of qualitative indicators, there were identified 5 winter durum wheat samples, which are recommended to be included in the breeding programs of the Rostov region.